Twenty years of scientific production in sport and exercise psychology journals: A Bibliometric Analysis in Web of Science - Coimbra D.R. (2022)
© 2022 Sociedad Revista de Psicologia del Deporte. All rights reserved.The present study analyzed the last twenty years (2001 to 2020) of scientific production in sport and exercise psychology (SEP) journals indexed in Web of Science. Ten journals were selected. Psychology of sport and exercise was the journal with the highest number of articles per year (n = 82). USA was the most productive country (n = 1553). University of Birmingham (n = 195) was the institution most prolific, and Social Sciences and Humanities Research Council of Canada (n = 239)was the funding agency most present. Nikos Ntoumanis (n = 67) was the most prolific author. Physical activity (n = 326) was the keyword with most occurrences. Open access represents 27.24% of articles. We concluded that the majority of journals published in the English language and with no open access. Self-determination theory is a well consolidated theoretical framework in the last twenty years in SEP journals.